Cement-free high-purity tin bath combined top cover brick and preparation method thereof

Through the design of cementless high-purity tin tank combination top cover bricks, using specific raw material combinations and preparation methods, the existing tin tank top cover bricks have been solved, and the problems of high impurity content, low load softening temperature, low refractory resistance and poor thermal shock resistance are achieved, and higher refractory resistance, thermal shock stability and service life are achieved.

CN119707470APending Publication Date: 2025-03-28ZHENGZHOU ZHENFA NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411417245.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing float glass production lines, the tin tank top cover bricks have problems such as high impurity content (especially CaO content), low load softening temperature, low refractory resistance and poor thermal shock resistance.

Method used

The cementless high-purity tin tank combination top cover brick is made of raw material mullite aggregate, zircon sand, alumina powder, mineralizer and mullite fine powder. The cement is removed and other raw material components are redistributed to improve the material's refraction and thermal shock stability.

Benefits of technology

It effectively improves the fire resistance and thermal shock stability of bricks, reduces the porosity, ensures the service effect and service life, and enhances the heat insulation effect and mechanical strength, and improves the flexural strength and pressure resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of top cover brick production, in particular to a cement-free high-purity tin bath combined top cover brick and a preparation method thereof.The cement-free high-purity tin bath combined top cover brick is prepared from, by mass, 45%-50% of mullite aggregate, 5%-10% of zircon sand, 20%-25% of alumina micro powder, 4%-5% of mineralizer and 15%-20% of mullite fine powder; according to the cement-free high-purity tin bath combined top cover brick, the finished brick is prepared by removing cement and redistributing other raw material components and mass, the refractoriness and thermal shock resistance of the finished brick can be effectively improved, meanwhile, the apparent porosity of the finished brick is effectively reduced, and the using effect and the service life of the finished brick are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of roof brick production, and in particular relates to a cement-free high-purity tin bath combined roof brick and a preparation method thereof. Background Art

[0002] Cement-free high-purity tin bath combined top brick is a high-performance refractory material specially designed for the tin bath in the float glass production line. The main feature of this brick is that it can still maintain excellent high temperature resistance, chemical stability and mechanical strength without using traditional cement binders.

[0003] In the prior art, the tin bath is a key part of the float glass production line, which is mainly composed of the tin bath bottom and the tin bath cover, and is used to support and transfer the molten glass liquid. At present, the combined cover bricks for the tin bath of the float glass production line are generally cast and formed by aluminosilicate refractory materials. For example, the Chinese invention patent with application number 201410534146.4 and invention name "A low thermal conductivity mullite tin bath combined cover brick" needs to add cement during production, thereby introducing about 2% of CaO. The introduction of CaO will have a reverse effect on the refractoriness and thermal shock resistance of the tin bath cover brick. At the same time, the addition of cement will affect the apparent porosity of the brick, thereby affecting its use effect and service life. Therefore, how to overcome the above-mentioned technical problems and defects has become a key problem to be solved. Summary of the invention

[0004] The object of the present invention is to overcome the defects described in the background technology, thereby realizing a cement-free high-purity tin bath composite cover brick, which is used to solve the problems of high impurity content (especially CaO content), low load softening temperature, low refractoriness and poor thermal shock resistance of tin bath cover bricks in the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is: A cement-free high-purity tin bath combined top cover brick is made of 45% to 50% of raw materials of mullite aggregate, 5% to 10% of zircon sand, 20% to 25% of alumina powder, 4% to 5% of mineralizer, and 15% to 20% of mullite fine powder in percentage by mass.

[0006] In the above-mentioned cement-free high-purity tin bath composite top cover brick, preferably, the cement-free high-purity tin bath composite top cover brick is made of 46% raw materials of mullite aggregate, 5% of zircon sand, 25% of alumina powder, 4% of mineralizer, and 20% of mullite fine powder, by mass percentage.

[0007] Specifically, the mineralizer is andalusite.

[0008] In the above-mentioned cement-free high-purity tin bath composite top cover brick, preferably, the cement-free high-purity tin bath composite top cover brick is made of 50% raw material mullite aggregate, 8% zircon sand, 22% alumina powder, 5% mineralizer, and 15% mullite fine powder, by mass percentage.

[0009] Specifically, the mineralizer is sillimanite.

[0010] In the above-mentioned cement-free high-purity tin bath composite top cover brick, preferably, the cement-free high-purity tin bath composite top cover brick is made of 48% raw materials mullite aggregate, 10% zircon sand, 20% alumina powder, 5% mineralizer, and 17% mullite fine powder, by mass percentage.

[0011] Specifically, the mineralizer consists of 2% andalusite and 3% sillimanite.

[0012] In the above-mentioned cement-free high-purity tin bath combined top cover brick, in the mullite aggregate, the mass percentage of Al2O3 is ≥55%, and the mass percentage of Fe2O3 is ≤0.5%.

[0013] In the above-mentioned cement-free high-purity tin bath combined top cover brick, the particle size of the mullite aggregate is 0.088-8 mm, and the volume density is 2.65-2.85 g / cm 3 , the apparent porosity is 2% to 5%, the average pore diameter D50 is ≤ 12 μm, and the mass percentage of the mullite phase is ≥ 65%.

[0014] In the above-mentioned cement-free high-purity tin bath combined top cover brick, in the mullite fine powder, the mass percentage of Al2O3 is ≥50%, the mass percentage of Fe2O3 is ≤0.5%, and the sum of the mass percentages of Na2O and K2O is ≤0.5%.

[0015] In the above-mentioned cement-free high-purity tin bath combined top cover brick, the particle size of the zircon sand is 0.1-1 mm, and the particle size of the mineralizer is 0.1-0.5 mm.

[0016] In the above-mentioned cement-free high-purity tin bath combined top cover brick, the fineness of the alumina powder is 1000 mesh, and the fineness of the mullite powder is 320 mesh.

[0017] The present invention also discloses a method for preparing the above-mentioned cement-free high-purity tin bath combined top cover brick, and the preparation method comprises: Step 1: Mixing raw materials: feeding the raw materials into a mixing device, adding a binder and stirring to form a mixture, stirring for 15min-20min, wherein the mass percentage content of the binder in the mixture is 3%-6%.

[0018] Step 2: pressing and molding; placing the mixed raw materials in the mold of a press, controlling the CNC friction press to perform pressing and molding, the pressing speed of the CNC friction press is 15-20 times / min, the pressure holding time is 10-15s / time, the friction wheel speed of the CNC friction press is 2000-3000 rpm, and after demolding, curing under natural conditions (or standard curing), and then drying at 110°C, and then sintering at high temperature in a tunnel kiln or a downdraft kiln to obtain the cement-free high-purity tin bath combined top cover brick.

[0019] Step 3: demoulding and drying; placing the pressed bricks in a drying room for natural drying or forced ventilation drying, the drying temperature is 80-120°C, and the drying time is 12-24h.

[0020] Step 4: kiln firing; the dried bricks are sent to a tunnel kiln or a downdraft kiln for high-temperature sintering, and the heating rate of the tunnel kiln or the downdraft kiln is 50-100°C / h.

[0021] Step 5: Cooling the bricks. After firing, slowly cool the bricks to room temperature in the kiln at a cooling rate of 20-50°C / h.

[0022] Compared with the prior art, the cement-free high-purity tin bath combined top cover brick of the present invention has at least the following beneficial effects: 1. The cement-free high-purity tin bath combined top cover brick of the present invention is made into a brick by removing cement and redistributing other raw material components and masses, which can effectively improve the refractoriness and thermal shock stability of the brick, and effectively reduce the apparent porosity of the brick, thereby ensuring the use effect and service life of the brick; 2. By enhancing the thermal insulation effect and ensuring the mechanical strength of the material, it can prevent it from being affected by external stress. The flexural strength and compressive strength are high, which increases its service life while improving its thermal efficiency and reducing energy consumption. The high thermal shock stability can effectively ensure the stability of the structure, prevent structural damage during use, ensure the safe operation of the equipment, and reduce maintenance workload and costs; 3. By redistributing the raw materials, the resulting bricks have enhanced flexural strength, which prevents them from breaking when subjected to bending loads. High compressive strength has a strong load-bearing capacity and prevents the material from losing structural stability under high temperature and high pressure environments, leading to equipment failure. DETAILED DESCRIPTION

[0023] The cement-free high-purity tin bath combined top cover brick of the present invention is described in more detail below through specific implementation methods.

[0024] Example 1 The present embodiment discloses a cement-free high-purity tin bath combined top brick, which is used to solve the problems of high impurity content (especially CaO content), low refractoriness under load, low refractoriness and poor thermal shock resistance of the tin bath top brick in the prior art. In the present embodiment, the above-mentioned cement-free high-purity tin bath combined top brick is made of 45% to 50% of raw material mullite aggregate, 5% to 10% of zircon sand, 20% to 25% of alumina powder, 4% to 5% of mineralizer, and 15% to 20% of mullite fine powder in terms of mass percentage.

[0025] In this embodiment, the high temperature resistance and corrosion resistance of the brick can be significantly improved by adding zircon sand, especially the stability at high temperature. At the same time, the brick is prepared by mullite aggregate, alumina powder, mineralizer, and mullite fine powder. The high purity of all main components ensures the high temperature stability and chemical stability of the material and reduces the influence of impurities.

[0026] It should be noted that in the mullite aggregate described in this embodiment, the mass percentage of Al2O3 is ≥55%, and the mass percentage of Fe2O3 is ≤0.5%. The use of mullite aggregate with high Al2O3 makes the brick have good high temperature resistance and chemical stability, which can effectively improve the melting point and corrosion resistance. The mass percentage of Fe2O3 is ≤0.5%, which reduces the influence of iron oxide on the high temperature performance of the material and improves the purity of the material.

[0027] Meanwhile, the particle size of the mullite aggregate is 0.088-8 mm, and the bulk density is 2.65-2.85 g / cm 3 , the apparent porosity is 2% to 5%, the average pore diameter D50 is ≤ 12 μm, and the mass percentage of the mullite phase is ≥ 65%. 3 The mullite aggregate effectively improves the compactness of the internal structure of the material, which helps to further improve the fire resistance and erosion resistance. At the same time, the average pore diameter D50 is ≤12μm. The small pore diameter helps to reduce heat conduction loss and improve thermal insulation performance. The mass percentage of mullite phase is ≥65%, which ensures the stability and structural strength of the material at high temperatures.

[0028] In addition, in the mullite fine powder, the mass percentage of Al2O3 is ≥50%, providing good high temperature resistance and chemical stability. The mass percentage of Fe2O3 is ≤0.5%, and the sum of the mass percentages of Na2O and K2O is ≤0.5%, controlling the content of alkali metals and reducing the volatility of the material at high temperatures.

[0029] In the alumina micropowder, the mass percentage of Al2O3 is ≥99.5%. The extremely high purity makes the material have excellent high temperature resistance and chemical corrosion resistance. The mass percentage of Fe2O3 is ≤0.1%, and the mass percentage of Na2O is ≤0.1%. The fineness of the alumina micropowder is 1000 mesh, and the fineness of the mullite fine powder is 320 mesh. The fine powder helps to fill the gaps between particles and improve the density of the material.

[0030] Specifically, in this embodiment, the cement-free high-purity tin bath combined top cover brick is made of 46% raw material mullite aggregate, 5% zircon sand, 25% alumina powder, 4% mineralizer, and 20% mullite fine powder by mass percentage. The mineralizer is andalusite.

[0031] By adding a high proportion of alumina powder, the overall density of the material is effectively improved, providing good corrosion resistance. At the same time, a high proportion of mullite fine powder can help enhance the structural strength of the material, and the use of andalusite as a mineralizer will mullite at high temperatures to form a staggered and compact mullite structure, which helps to improve thermal shock stability.

[0032] The cement-free high-purity tin bath composite top cover brick made of the above weight percentage components is suitable for occasions that have certain requirements on strength and corrosion resistance but are more cost-sensitive, such as general top covers.

[0033] This embodiment also discloses a method for preparing the cement-free high-purity tin bath combined top cover brick with the above weight percentage components, comprising the following steps: Step 1: Mixing raw materials: feeding the raw materials into a mixing device, adding a binder and stirring to form a mixture, stirring for 15min-20min, wherein the mass percentage content of the binder in the mixture is 3%-6%.

[0034] Step 2: pressing and molding; placing the mixed raw materials in the mold of a press, controlling the CNC friction press to perform pressing and molding, the pressing speed of the CNC friction press is 15-20 times / min, the pressure holding time is 10-15s / time, the friction wheel speed of the CNC friction press is 2000-3000 rpm, and after demolding, curing under natural conditions (or standard curing), and then drying at 110°C, and then sintering at high temperature in a tunnel kiln or a downdraft kiln to obtain the cement-free high-purity tin bath combined top cover brick.

[0035] Step 3: demoulding and drying; placing the pressed bricks in a drying room for natural drying or forced ventilation drying, the drying temperature is 80-120°C, and the drying time is 12-24h.

[0036] Step 4: kiln firing; the dried bricks are sent to a tunnel kiln or a downdraft kiln for high-temperature sintering, and the heating rate of the tunnel kiln or the downdraft kiln is 50-100°C / h.

[0037] Step 5: Cooling the bricks. After firing, slowly cool the bricks to room temperature in the kiln at a cooling rate of 20-50°C / h.

[0038] The cement-free high-purity tin bath combined top cover bricks with the above weight percentage components are prepared through the above steps. The high purity of the main components ensures the high temperature stability and chemical stability of the material and reduces the influence of impurities. And by using high-purity mullite aggregate, zircon sand and alumina powder, the load softening temperature of the material is increased, and the structural stability and high temperature resistance of the material are enhanced. At the same time, the addition of high-purity alumina powder and zircon sand improves the refractoriness of the material, enabling it to maintain structural integrity at higher temperatures. And it can effectively reduce heat conduction losses and improve thermal insulation effects, thereby improving the overall performance of the material.

[0039] Example 2 The same points as the above embodiment will not be repeated here, but the difference is that: In this embodiment, the cement-free high-purity tin bath combined top cover brick is made of 50% raw material mullite aggregate, 8% zircon sand, 22% alumina powder, 5% mineralizer, and 15% mullite fine powder by mass percentage. The mineralizer is sillimanite.

[0040] By adding a high proportion of mullite aggregate, the overall strength of the brick is effectively improved. At the same time, using sillimanite as a mineralizer, it shows better stability and durability in working environments with large temperature changes and extreme high temperature environments.

[0041] The cement-free high-purity tin bath composite top cover bricks made of the above-mentioned weight percentage components have higher strength and show better stability and durability in working environments with large temperature changes and extreme high temperature environments. They are suitable for occasions that need to withstand large mechanical loads, such as load-bearing parts of high-temperature furnaces.

[0042] Example 3 The same points as the above embodiment will not be repeated here, but the difference is that: In this embodiment, the cement-free high-purity tin bath combined top cover brick is made of 48% raw material mullite aggregate, 10% zircon sand, 20% alumina powder, 5% mineralizer, and 17% mullite fine powder by mass percentage. The mineralizer is composed of 2% andalusite and 3% sillimanite.

[0043] By adding a high proportion of zircon sand, the thermal shock stability is significantly improved, and the finished bricks have the best thermal shock stability. The high content of zircon sand can improve the resistance of the bricks to most acid and alkali solutions, molten metals and glass, thereby significantly improving the corrosion resistance and ensuring the chemical stability and structural integrity of the top cover bricks in long-term use; at the same time, zircon sand helps to reduce heat loss and improve energy efficiency. At the same time, the use of mineralizers composed of andalusite and sillimanite, andalusite can provide early protection at lower temperatures, while sillimanite can further enhance the thermal shock resistance of the material at higher temperatures, ensuring that the top cover bricks have good thermal shock resistance over the entire temperature range. At the same time, the use of mineralizers composed of andalusite and sillimanite can ensure that the top cover bricks have excellent refractoriness in high-temperature operating environments, thereby extending their service life. The characteristics and advantages of andalusite and sillimanite complement each other, thereby providing more superior performance.

[0044] The bricks made of the above-mentioned mass percentage components have a relatively balanced proportion of each component, which is conducive to the overall optimization of material properties and has good comprehensive performance. They are suitable for occasions with comprehensive and high requirements on material properties, such as the thermal insulation layer of precision instruments or high-temperature experimental equipment.

[0045] In summary, the following Table 1 is obtained:

[0046] The performance test results of the cement-free high-purity tin bath combined top cover bricks prepared according to the above Table 1 are as follows:

[0047] From Table 1 and Table 2 above, we can conclude that: The ingredients and content percentages of control group 1 and control group 2 are different from those of embodiments 1, 2, and 3, and the effects obtained are different from those of the bricks produced. Since the calcium aluminate cement content of control group 1 and control group 2 is too high, the apparent porosity of the bricks produced is relatively high, which will increase the thermal conductivity of the material, reduce the thermal insulation effect, and reduce the mechanical strength of the material, making it more susceptible to external stress. The flexural strength and compressive strength are low, and the low refractoriness will shorten the service life, reduce thermal efficiency, and increase energy consumption. The poor thermal shock stability leads to structural instability, and structural damage is prone to occur during use, affecting the safe operation of the equipment and increasing the maintenance workload and cost. The flexural strength is low, and it is more likely to break when subjected to bending loads. The low compressive strength has insufficient load-bearing capacity, and it is easy to deform or break when under pressure, and cannot withstand the predetermined load. At the same time, the material is prone to lose structural stability under high temperature and high pressure environments, leading to equipment failure. There is a big gap compared to embodiments 1, 2, and 3.

[0048] The bricks made of the components of Examples 1, 2, and 3 have a low apparent porosity, which can effectively reduce thermal conductivity, enhance thermal insulation, and ensure the mechanical strength of the material to prevent it from being affected by external stress. The flexural strength and compressive strength are high, which increases its service life while improving its thermal efficiency and reducing energy consumption. The high thermal shock stability can effectively ensure the stability of the structure, prevent structural damage during use, ensure the safe operation of the equipment, and reduce maintenance workload and costs.

[0049] At the same time, its high flexural strength prevents it from breaking when subjected to bending loads. High compressive strength provides a strong load-bearing capacity and prevents the material from losing structural stability in high temperature and high pressure environments, causing equipment failure.

[0050] It can be seen that the component contents of Examples 1, 2, and 3 are more reasonable, and Example 3 is the best example.

[0051] In addition, it should be noted that the preparation ingredients of Examples 1, 2, and 3 of this specification are not unique and unchanging data. This specification only lists the most representative mass percentage data of raw materials for preparing bricks with better performance and suitable for three different scenarios.

[0052] Unless otherwise defined, technical or scientific terms used herein shall have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs.

[0053] The exemplary implementation modes of the present invention are described in detail above with reference to the preferred embodiments. The protection scope of the present invention is not limited thereto. It can be understood by those skilled in the art that, without departing from the concept of the present invention, various modifications and variations can be made to the above-mentioned specific embodiments, and various combinations of the various technical features proposed in the present invention can be made without exceeding the protection scope of the present invention.

Claims

1. A cement-free high-purity tin bath combined top cover brick, characterized in that: The cement-free high-purity tin bath combined top cover brick is made of 45% to 50% of raw material mullite aggregate, 5% to 10% of zircon sand, 20% to 25% of alumina powder, 4% to 5% of mineralizer, and 15% to 20% of mullite fine powder in terms of mass percentage.

2. The cement-free high-purity tin bath combined top cover brick according to claim 1 is characterized in that: The cement-free high-purity tin bath combined top cover brick is made of 46% of raw materials of mullite aggregate, 5% of zircon sand, 25% of alumina powder, 4% of mineralizer, and 20% of mullite fine powder in terms of mass percentage; The mineralizer is andalusite.

3. The cement-free high-purity tin bath combined top cover brick according to claim 1 is characterized in that: The cement-free high-purity tin bath combined top cover brick is made of 50% raw material mullite aggregate, 8% zircon sand, 22% alumina powder, 5% mineralizer, and 15% mullite fine powder in terms of mass percentage; The mineralizer is sillimanite.

4. The cement-free high-purity tin bath combined top cover brick according to claim 1 is characterized in that: The cement-free high-purity tin bath combined top cover brick is made of 48% of raw materials mullite aggregate, 10% of zircon sand, 20% of alumina powder, 5% of mineralizer, and 17% of mullite fine powder in terms of mass percentage; The mineralizer consists of 2% andalusite and 3% sillimanite.

5. The cement-free high-purity tin bath combined top cover brick according to any one of claims 1 to 4, characterized in that: In the mullite aggregate, the mass percentage of Al2O3 is ≥55%, and the mass percentage of Fe2O3 is ≤0.5%.

6. The cement-free high-purity tin bath combined top cover brick according to any one of claims 1 to 4, characterized in that: The particle size of the mullite aggregate is 0.088-8 mm, and the bulk density is 2.65-2.85 g / cm 3 , the apparent porosity is 2% to 5%, the average pore diameter D50 is ≤ 12 μm, and the mass percentage of the mullite phase is ≥ 65%.

7. The cement-free high-purity tin bath combined top cover brick according to any one of claims 1 to 4, characterized in that: In the mullite fine powder, the mass percentage of Al2O3 is ≥50%, the mass percentage of Fe2O3 is ≤0.5%, and the sum of the mass percentages of Na2O and K2O is ≤0.5%.

8. The cement-free high-purity tin bath combined top cover brick according to any one of claims 1 to 4, characterized in that: The particle size of the zircon sand is 0.1-1 mm, and the particle size of the mineralizer is 0.1-0.5 mm.

9. The cement-free high-purity tin bath combined top cover brick according to any one of claims 1 to 4, characterized in that: The mullite fine powder has a fineness of 320 meshes, and the alumina fine powder has a fineness of 1000 meshes.

10. A method for preparing a cement-free high-purity tin bath combined top cover brick, characterized in that: Step 1: Mixing raw materials: feeding the raw materials into a mixing device, adding a binder and stirring to form a mixture, stirring for 15-20 minutes, wherein the mass percentage of the binder in the mixture is 3%-6%; Step 2: pressing and molding; placing the mixed raw materials in a mold of a press, controlling a CNC friction press to perform pressing and molding, wherein the pressing speed of the CNC friction press is 15-20 times / min, the holding time is 10-15s / time, and the friction wheel speed of the CNC friction press is 2000-3000 rpm. After demolding, curing is performed under natural conditions (or standard curing), and then drying is performed at 110°C, and then high-temperature firing is performed in a tunnel kiln or a downdraft kiln to obtain the cement-free high-purity tin bath combined top cover brick; Step 3: demoulding and drying; placing the pressed bricks in a drying room for natural drying or forced ventilation drying, the drying temperature is 80-120°C, and the drying time is 12-24h; Step 4: kiln firing; the dried bricks are sent to a tunnel kiln or a downdraft kiln for high-temperature sintering, and the heating rate of the tunnel kiln or the downdraft kiln is 50-100°C / h; Step 5: Cooling the bricks. After firing, slowly cool the bricks to room temperature in the kiln at a cooling rate of 20-50°C / h.

Citation Information

Patent Citations

  • Low-thermal-conductivity mullite tin bath combined top cover brick

    CN104326755A